G61(P) What should trusts charge NHS England to deliver specialist inpatient neurorehabilitation in the setting of a regional paediatric neuroscience centre?. (25th October 2020) - Sharples, PM; Shuyu, L; Spray, A; Smith, HK
Abstract : Aims: To calculate what bed-day tariff a paediatric Regional Neuroscience Centre (RNSC) should charge to deliver a quality, sustainable specialist in-patient neurorehabilitation service, taking into account patient complexity/dependency. Methods: Ethical approval was obtained from University of Southampton. Anonymized data on children receiving in-patient neurorehabilitation at a paediatric RNSC 1/6/2017–31/5/2019 were analyzed. Patient dependency and rehabilitation complexity was assessed by Rehabilitation Complexity Scale (RCS); this provides an overall measure of Care or Risk, Nursing, Therapy, Medical and Equipment needs. RCS-Extended (version-13) was scored for neurorehabilitation patients jointly by multi-disciplinary team members at weekly clinical meetings. RCS-E scores were categorized as: very low level of rehabilitation need (0–4); low level (5–8); medium level (9–12); high level (13–16); very high level (17–22). Discrete-Event Simulation (DES) was used to simulate in-patient neurorehabilitation service work flow, calculating how many patients would be treated each day and their changing rehabilitation needs. Staffing numbers required were based on the modelling results, applying published minimum staffing provisions for adult neurorehabilitation centers. Service costs and bed-day tariffs were calculated from calculated staff numbers, assuming 25% overheads. Results: The database contained 114 children who received inpatient neurorehabilitation over the two-year study period. 21 had no RCS data; 29 others were admitted before the study period, 4 discharged afterwards. Excluding these patients, 69 were used in the model, which mapped routes between dependency levels. Modelling showed 91 patients to be admitted and discharged by the neurorehabilitation service over two years (95% CI 75–107). Mean Length of Stay=53 days (95% CI 44–62). Mean number of beds occupied at any one time by neurorehabilitation in-patients=6.3 (95% CI 4-8-8.0). Of these, 0.65 (95% CI 0.17–1.26) were occupied by patients with very high needs; 1.73 (CI 1.08–2.45) high needs; 2.25 (CI 1.58-2-91) medium needs; 0.20 (CI 0.13–0.28) low needs; 0.0.8 (CI 0.02–0.17) very low needs. Applying differential published adult staffing standards to the modelled complexity/dependency levels and assuming 25% overheads, the bed-day tariff required to support the specialist neurorehabilitation in-patient service ranged from £622.45-£754.75. Conclusions: Application of simulation modelling to real-world paediatric data suggests costs in keeping with those charged by adult centers.